Thar Vaibhav: A new bunch bearing variety of acid lime - Mishra, DAYA SHANKAR; Sanjay Singh; Vikas Yadav; B. D. Sharma (Indian Horticulture, 2022)
Thar Vaibhav, is an acid lime variety, developed at Central Horticultural Experiment Station (ICAR-CIAH), Vejalpur, Godhra, Gujarat. It is a precocious and prolific bunch bearing variety of acid lime having vigorous and spreading growth habit with low density of spines. Fruits are round with attractive yellowish smooth peel. Fruit is juicy (49%), acidic (6.84%) with less number of seeds/fruit (6-8). It starts flowering and fruiting during 3rd year of its planting, and bears fruits mostly on the periphery of the canopy. It is high yielder with an average yield/plant of 60.15 kgduring 6th year of planting under rainfed hot semi-arid conditions in western India. Fruit ripens in 125-135 days in summer while rainy season and w inter season crop may take 145-155 days from fruit set with excellent keeping quality at ambient storage. On an average, it bears 3-9 fruits/bunch and such varieties are in great demand by acid lime growers of country, therefore, it was released to satisfy the needs of growers.